38th AIAA/ASME/SAE/ASEE Joint Propulsion Conference &Amp;amp; Exhibit 2002
DOI: 10.2514/6.2002-3999
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Side Load Phenomena Using Measurement of Fluid/Structure Interaction

Abstract: During ground-tests of most production rocket engines over the last 30 years, large asymmetric transient side loads coming from the nozzle and related steady-state vibrational loads within the nozzle have been measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…Once the flow reattaches, the flow expands and the pressure decreases up to the second separation point. [12] suggested that additional sources of side load disturbances are produced by fluctuating wall pressures in the separated regions of the nozzle, as well as aeroelastic fluid structure coupling; the latter was studied experimentally by Brown et al [13]. Numerical models have also been developed to provide more insight into the origin of side loads during the full duty cycle of the engine.…”
mentioning
confidence: 99%
“…Once the flow reattaches, the flow expands and the pressure decreases up to the second separation point. [12] suggested that additional sources of side load disturbances are produced by fluctuating wall pressures in the separated regions of the nozzle, as well as aeroelastic fluid structure coupling; the latter was studied experimentally by Brown et al [13]. Numerical models have also been developed to provide more insight into the origin of side loads during the full duty cycle of the engine.…”
mentioning
confidence: 99%
“…As an aside, we note that rocket body vibrations, particularly those involving the nozzle or its attachments, can play a significant role in nozzle side load generation (Brown et al 2002). Because side loads, in turn, represent an important dynamical feature, the impact of rocket vibration on ascent constitutes an important open question.…”
Section: Analogue Self-propelled Brownian Oscillator (A) Overview Of mentioning
confidence: 99%
“…In large engines, side loads can reach extreme magnitudes, for example, of the order of 250 000 pounds in Apollo Saturn V rockets (Brown et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem has been well studied through experiments as well as computations. The unsteady separation phenomenon inside the nozzle can lead to steady/unsteady forcing of the thrusting nozzle, as well as associated mechanisms due to fluid-structure interactions [1][2][3][4][5]. The presence of such unsteady side loads can also result in adverse control systems of the vehicle in pitch, roll, and yaw [6].…”
Section: Introductionmentioning
confidence: 99%